Synthesis and Application of Isatin Schiff Base as Corrosion Inhibitor - Hao, Huarui; Xue, Chenghu; Miao, Yanqing; Zhang, Zhifang (Asian Journal of Chemistry, 2014)
Isatin Schiff base, 3-(4-hydroxyphenylimino)indolin-2-one, was synthesized and analyzed by NMR and MS. The inhibition and the mechanism of the title compound on the corrosion of high protective Q235A steel in HCl solution were screened and discussed. The results indicated that it can inhibit the corrosion with moderate inhibition efficiency in different conditions and the inhibition mechanism of the corrosion inhibiting may be mainly contributed to the adsorption. While the isatin Schiff base was companied with hexamethylenetetramine (HMTA) and 1,4-dihydroxy-2-butyne (BOZ), the inhibition efficiency was enhanced effectively.